Involvement of NPOs in providing social sphere services - Рудник, Борис; Куштанина, Елена; Романова, Вера (Public Administration Issues, 2017)
Involving non-profit organizations (NPOs) in providing state and municipal services in the social sphere (including education, healthcare, culture and social policy, physical culture and sport, mass media) has been a priority of Russia’s social policy for the past several years. However, there has been no significant progress achieved in dealing with this issue, as evidenced by the fact that the need for such involvement has been repeatedly underlined in the speech of the President of the Russian Federation addressed to the Federal Assembly (2013–2015). According to statistics, the volume of subsidiaries allocated to private organizations in the social sphere amounted to only 40 billion rubles in 2015 or 1.6% of the total funds allocated to this area in the federal budget. In comparison with 2013, it decreased by almost 15%.The article presents the results of a research of socio-economic mechanisms of involving NPOs in providing services in the social sphere. This article considers more specifically the level of real functioning of these mechanisms in the subjects of the Russian Federation, through analyzing the indicators of amount and structure of the budget allocations to NPOs. These mechanisms are analyzed on the federal and regional levelsthrough the scope of: a) the rights (and the duties) of the state (municipal) authorities to involve NPOs in providing social services at the expenses of budget funds; b) the procedures of service providers selection; c) the method (tool) of NPOs budgeting.The article specifies deficiencies of these mechanisms that determine obstacles to a wider involvement of NPOs in providing social services. One of these obstacles is the low «status» of the services provided by NPOs. Today, they are often not formally related to the state (municipal) services ensuring the realization of social guarantees.